2022
DOI: 10.1002/jbt.23290
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of novel N‐(4‐aminobenzoyl)‐l‐glutamic acid conjugated 1,3,5‐triazine derivatives as Pf‐DHFR inhibitor: An in‐silico and in‐vitro study

Abstract: In the present work, a library of 120 compounds was prepared using various aliphatic and aromatic amines. Finally, 10 compounds were selected through in silico screening carrying 4‐aminobenzoyl‐l‐glutamic acid and 1,3,5‐triazine moiety. The docking results of compounds 4d16 and 4d38 revealed higher binding interaction with amino acids Asp54 (−537.96 kcal/mol) and Asp54, Phe116 (−618.22 kcal/mol) against wild (1J3I) and quadruple mutant (1J3K) type of Pf‐DHFR inhibitors and were comparable to standard WR99210. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…3.1.2. General Procedure for the Synthesis of Disubstituted Triazines (8)(9)(10)(11) The synthesis of derivatives 8 [74], 9 [71] and 11 [73] was reported in previous studies. Disubstituted triazine 10 was obtained as follows: 4-hydroxy-3-methoxybenzaldehyde (13 mmol)was added slowly to a solution of monosubstituted triazine 6 (13 mmol) in acetone (35 mL) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1.2. General Procedure for the Synthesis of Disubstituted Triazines (8)(9)(10)(11) The synthesis of derivatives 8 [74], 9 [71] and 11 [73] was reported in previous studies. Disubstituted triazine 10 was obtained as follows: 4-hydroxy-3-methoxybenzaldehyde (13 mmol)was added slowly to a solution of monosubstituted triazine 6 (13 mmol) in acetone (35 mL) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, using a three-step synthetic sequence, the trisubstituted triazine precursors 12-15 were synthesized by aromatic nucleophilic substitution reactions (Ar N S) from 2,4,6trichloro-1,3,5-triazine 4 [50,[68][69][70][71][72][73][74][75] (Table 1). Looking for structural diversity, substituents of aliphatic and aromatic nature and functional groups capable of forming hydrogen bonding were incorporated.…”
Section: Chemistrymentioning
confidence: 99%
“…Likewise, a new series of 120 compounds of N -(4-aminobenzoyl)- l -glutamic acid pendant s -triazine (80) was successfully synthesized via microwave-assisted synthesis techniques in good yield. 97 Before in vitro analysis, these compounds were evaluated through in silico modeling and only 10 compounds out of 120 were selected for further screening. Through SAR analysis, it was observed that this series possessed two main hits, one with piperidine and one with piperazine moiety.…”
Section: Biological Activities Of S -Triazine-base...mentioning
confidence: 99%